Palmar fasciitis and polyarthritis syndrome-Systematic literature review of 100 cases - Manger, Bernhard; Schett, Georg (Seminars in Arthritis and Rheumatism, 2014)
To analyse clinical, laboratory, and imaging characteristics of all patients with palmar fasciitis and polyarthritis syndrome (PFPAS) described in the literature.Comparison of the clinical presentation of one patient with acute onset of PFAPS with 99 other published cases identified through a PubMed literature research.Since the original description in 1982 by Medsger et al., there have been numerous case reports and small case series in the literature. In total, 73 articles in English, French and Spanish language were included in the analysis. PFPAS is a rare but characteristic paraneoplastic syndrome in rheumatology. Its distinct clinical feature is a painful swelling of both the hands caused by an inflammation of the palmar fascia, tendon sheaths and small joints of fingers and wrist, and flexion contractures develop rapidly. Since the subcutaneous tissues become indurated and hard, the illustrative term "woody hands" was coined. The most frequent underlying malignancy is ovarian cancer but adenocarcinomas of the breast, gastrointestinal tract and other organs can also cause this syndrome. A helpful diagnostic procedure in order to identify the nature of the underlying malignancy in many cases has been the determination of various serum tumour markers. In cases when a complete removal of the malignancy is possible, PFPAS can also undergo complete remission.Knowledge of the distinct features of this rare paraneoplastic syndrome facilitates early diagnosis and potentially life-saving therapeutic interventions.
EVALuna2:12992